10kv cable low-smoke halogen-free flame-retardant sheath material and preparation method thereof
Patent Information
- Application Number
- CN202611057550.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-07-16
AI Technical Summary
然而,该技术方案中无机阻燃材料的用量很大,不同阻燃颗粒主要以独立形式分散于聚合物基材中,存在颗粒团聚和界面缺陷的问题,进而影响护套材料的机械性能和阻燃性能
本发明以聚磷酸铵为原料,经正硅酸四乙酯和乙烯基三乙氧基硅烷水解缩合形成硅氧中间层,再利用九水合硝酸铝在其表面沉积氢氧化铝外层,得到具有聚磷酸铵内核、硅氧中间层和氢氧化铝外层的阻燃母粒。硅氧中间层可隔离聚磷酸铵内核,并通过Si-O-Al界面结构固定氢氧化铝外层;氢氧化铝外层的羟基与EVA265相互作用,有利于促进阻燃母粒在聚乙烯基材中的分散。燃烧时,氢氧化铝和氢氧化镁吸热分解并生成Al2O3和MgO,聚磷酸铵催化双季戊四醇及部分聚乙烯基材脱水成炭,三聚氰胺尿酸盐分解释放不燃性气体并促进炭层形成;硅氧结构与Al2O3和MgO共同增强炭层的致密性和完整性,从而提高护套材料的抑烟性能和阻燃性能。
Smart Images

Figure SMS_7
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer flame retardant materials, specifically to a low-smoke, halogen-free flame retardant sheath material for 10kV cables and its preparation method. Background Technology
[0002] As power transmission and distribution systems develop towards higher safety, lower smoke, and halogen-free characteristics, 10kV cable sheath materials not only need stable electrical properties but also good flame retardant, smoke suppression, and mechanical properties. Polyethylene, with its good electrical insulation and processing properties, is widely used in cable sheath materials. However, polyethylene has a low limiting oxygen index, making it prone to melting and dripping during combustion and flame propagation, which makes it difficult to directly meet the requirements for low-smoke halogen-free flame-retardant cable sheath materials.
[0003] Existing polyethylene-based low-smoke halogen-free flame-retardant sheathing materials typically incorporate inorganic flame-retardants such as aluminum hydroxide and magnesium hydroxide. Aluminum hydroxide and magnesium hydroxide can endothermally decompose and release moisture upon heating, lowering the material's surface temperature and diluting flammable gases, offering advantages such as halogen-free and low-smoke properties. However, the flame-retardant efficiency of these inorganic materials is relatively low, usually requiring higher addition amounts to achieve good flame-retardant effects. Large quantities of inorganic flame-retardant particles are prone to agglomeration within the polymer matrix, forming interfacial defects that affect the mechanical properties of the sheathing material. An intumescent flame-retardant system composed of ammonium polyphosphate, a charring agent, and a nitrogen-containing foaming agent can form an expanded char layer through the synergistic effect between the acid source, char source, and gas source, effectively blocking heat, oxygen, and flammable products, thus reducing the amount of inorganic flame-retardant materials used. However, ammonium polyphosphate is prone to agglomeration within the polyethylene matrix, and its interfacial interaction with the polymer matrix is weak, also affecting the overall performance of the sheathing material.
[0004] For example, patent document CN112662042A discloses a B1-grade low-smoke halogen-free cable sheath material and its preparation method. It uses polyethylene resin and ethylene-octene copolymer as the matrix, and adds aluminum hydroxide, magnesium hydroxide, and a smoke-suppressing and char-forming agent to improve the flame-retardant properties of the sheath material. However, this technical solution uses a large amount of inorganic flame-retardant material, and different flame-retardant particles are mainly dispersed independently in the polymer matrix, resulting in particle agglomeration and interface defects, which in turn affect the mechanical and flame-retardant properties of the sheath material.
[0005] In summary, there is a need to provide a low-smoke, halogen-free flame-retardant sheath material for 10kV cables and its preparation method, in order to solve the problems existing in the prior art. Summary of the Invention
[0006] In order to overcome the shortcomings and deficiencies of the existing technology, the present invention provides a low-smoke halogen-free flame-retardant sheath material for 10kV cables and its preparation method.
[0007] To achieve the above objectives, a method for preparing a low-smoke, halogen-free, flame-retardant sheath material for 10kV cables includes the following preparation steps: S1. Mix ammonium polyphosphate, anhydrous ethanol and deionized water evenly, adjust the pH to alkaline, add emulsifier, heat and stir, add tetraethyl orthosilicate, stir to react, add vinyltriethoxysilane, heat to react, filter, wash and dry, and after obtaining pretreated particles, pour into anhydrous ethanol to obtain a dispersion. S2. Dissolve aluminum nitrate nonahydrate in deionized water, pour into the dispersion, add urea, adjust the pH to weakly acidic, heat and stir, centrifuge, wash and dry, pulverize and sieve to obtain flame retardant masterbatch. S3. Mix polyethylene, EVA265, POE-g-GMA, aluminum hydroxide, magnesium hydroxide, flame retardant masterbatch, dipentaerythritol, melamine urate, antioxidant, silicone, polyethylene wax, zinc stearate and stearic acid evenly, knead, mold, cool and shape to obtain sheath material.
[0008] This invention uses ammonium polyphosphate as raw material, which undergoes hydrolysis and condensation with tetraethyl orthosilicate and vinyltriethoxysilane to form a silicon-oxygen interlayer, resulting in pretreated particles. Then, aluminum hydroxide is deposited on the surface of the pretreated particles using aluminum nitrate nonahydrate to obtain a flame-retardant masterbatch. Further, the flame-retardant masterbatch, along with dipentaerythritol, melamine urate, aluminum hydroxide, and magnesium hydroxide, is added to a polyethylene substrate to improve the flame-retardant properties of the sheath material. The silicon-oxygen interlayer isolates the ammonium polyphosphate core from the external environment and utilizes its surface silanol groups to adsorb aluminum ions and their hydrolysis products. This allows the aluminum-containing hydroxyl groups to be fixed to the surface of the silicon-oxygen interlayer through a Si-O-Al interface structure, thus combining the ammonium polyphosphate core, silicon-oxygen interlayer, and aluminum hydroxide outer layer into structurally stable composite particles. Simultaneously, the hydroxyl groups on the surface of the aluminum hydroxide outer layer interact with the polar groups in EVA265, thereby enhancing the interfacial interaction between the flame-retardant masterbatch and the polyethylene substrate, promoting the dispersion of the flame-retardant masterbatch in the polyethylene substrate, and reducing the agglomeration of the flame-retardant masterbatch. During combustion, the aluminum hydroxide outer layer of the flame-retardant masterbatch and the aluminum hydroxide and magnesium hydroxide in the sheath material decompose endothermically and release moisture, reducing the surface temperature of the material, diluting oxygen and combustible gases, and generating Al2O3 and MgO. The ammonium polyphosphate core decomposes under heat to form phosphoric acid and polyphosphoric acid, catalyzing the dehydration of dipentaerythritol and part of the polyethylene substrate into char. Melamine urate decomposes to release non-flammable gases and promotes the formation of the char layer. The silicon-oxygen intermediate layer forms a stable silicon-oxygen structure at high temperature and is distributed in the char layer together with Al2O3 and MgO, playing an inorganic skeleton reinforcing role in the char layer, thereby reducing local collapse of the char layer, improving the density and integrity of the char layer, enhancing the barrier effect of the char layer against heat, oxygen and combustible products, reducing molten dripping, and improving the smoke suppression and flame retardant properties of the sheath material.
[0009] This invention uses flame-retardant masterbatch to partially replace pure inorganic flame-retardant particles such as aluminum hydroxide and magnesium hydroxide. While maintaining the flame-retardant properties of the sheath material, it reduces the amount of pure inorganic flame-retardant particles used and improves the mechanical properties of the sheath material. Because the ammonium polyphosphate, silicon-oxygen interlayer, and aluminum hydroxide outer layer in the flame-retardant masterbatch are combined into structurally stable composite particles, it can reduce agglomeration and interface defects caused by the independent dispersion of different inorganic flame-retardant particles. Simultaneously, the aluminum hydroxide outer layer can interact with the polar groups in EVA265, which is beneficial for improving the dispersion uniformity and interfacial bonding strength of the flame-retardant masterbatch in the polyethylene matrix. This results in more uniform stress transmission when the sheath material is under stress, reducing stress concentration and crack initiation caused by inorganic particle agglomeration areas, thereby improving the tensile strength and elongation at break of the sheath material.
[0010] Optionally, in step S3, EVA265, aluminum hydroxide, magnesium hydroxide and flame retardant masterbatch are pre-mixed into a composite flame retardant, and then mixed evenly with other raw materials.
[0011] In this invention, EVA265 is used to wet and pre-disperse flame-retardant particles such as aluminum hydroxide, magnesium hydroxide, and flame-retardant masterbatch, reducing agglomeration caused by direct contact between the flame-retardant particles and making the dispersion of each flame-retardant particle in the subsequent polyethylene substrate more uniform. At the same time, the polar groups in EVA265 can form interfacial interactions with the outer layer of aluminum hydroxide on the surface of the flame-retardant masterbatch and the hydroxyl groups on the surfaces of aluminum hydroxide and magnesium hydroxide, enhancing the bonding between the flame-retardant particles and the polyethylene substrate, reducing interfacial defects and stress concentration, thereby improving the mechanical properties of the sheath material and facilitating the formation of a more uniform and complete char layer, further improving the flame-retardant and smoke-suppressing properties.
[0012] Optionally, the preparation method of the composite flame retardant includes the following steps: pouring EVA265 into a mixer, heating it to 100~110℃ for mixing and softening, mixing aluminum hydroxide, magnesium hydroxide and flame retardant masterbatch evenly, pouring it into the mixer in 3~5 batches, mixing at a speed of 20~30 rpm for 8~12 minutes, discharging and crushing to obtain the composite flame retardant.
[0013] In this invention, aluminum hydroxide, magnesium hydroxide and flame retardant masterbatch are mixed evenly and then added to EVA265 in 3 to 5 portions. This avoids local material accumulation and a sudden increase in mixing load caused by adding all at once, allowing each flame retardant particle to gradually enter the softened EVA265 and be fully sheared, which is beneficial to improving the uniformity of mixing.
[0014] Optionally, in step S3, polyethylene, POE-g-GMA, composite flame retardant, dipentaerythritol, melamine urate, antioxidant 1010, antioxidant 168, silicone, polyethylene wax, zinc stearate and stearic acid are mixed evenly, heated to 100~105℃ and kneaded for 15~20 minutes, then molded, cooled and shaped to obtain the sheath material.
[0015] Optionally, in step S1, ammonium type II polyphosphate, anhydrous ethanol, and deionized water are mixed evenly, ammonia is added to adjust the pH to 9.5-10, emulsifier OP-10 is added, the mixture is heated to 40-45°C, stirred at 400-500 rpm for 10-20 min, tetraethyl orthosilicate is added, and the mixture is stirred for 3-4 h, vinyltriethoxysilane is added, the mixture is heated to 60-65°C and stirred for 1-2 h, filtered, washed 3-4 times with anhydrous ethanol, and vacuum dried to obtain pretreated particles, which are then poured into anhydrous ethanol and stirred at 600-800 rpm for 20-30 min to obtain a dispersion.
[0016] In this invention, by controlling the alkaline conditions and reaction temperature, the hydrolysis and condensation of tetraethyl orthosilicate and vinyltriethoxysilane on the surface of ammonium polyphosphate can be promoted to form a silicon-oxygen intermediate layer; the emulsifier OP-10 and stirring treatment are beneficial to improving the dispersibility of ammonium polyphosphate, providing a basic condition for the uniform deposition of the subsequent aluminum hydroxide outer layer.
[0017] Optionally, in step S2, aluminum nitrate nonahydrate is dissolved in deionized water, poured into the dispersion, stirred at 400-600 rpm for 30-60 min, urea is added, and the pH is adjusted to 5.5-6 with acetate / sodium acetate buffer. The mixture is heated to 75-80℃ and stirred for 2-3 h. After centrifugation, the mixture is washed 2-3 times each with anhydrous ethanol and deionized water, vacuum dried, pulverized, and passed through a 200-mesh sieve to obtain flame retardant masterbatch.
[0018] Optionally, in step S3, polyethylene, POE-g-GMA, EVA265, aluminum hydroxide, magnesium hydroxide, flame retardant masterbatch, dipentaerythritol, melamine urate, antioxidant 1010, antioxidant 168, silicone, polyethylene wax, zinc stearate, and stearic acid are mixed evenly, heated to 100~105℃ and kneaded for 15~20 minutes, then molded, cooled and shaped to obtain the sheath material.
[0019] In this invention, aluminum hydroxide, magnesium hydroxide and flame retardant masterbatch are wetted and dispersed by EVA265, which improves the dispersion uniformity of each flame retardant particle in the polyethylene substrate, reduces particle agglomeration and interface defects, and thus improves the mechanical properties, flame retardant properties and smoke suppression properties of the sheath material.
[0020] Optionally, the molding process is carried out at a temperature of 150~160℃ and a pressure of 8~9MPa.
[0021] This invention also provides a 10kV cable low-smoke halogen-free flame-retardant sheath material, which is prepared by the above-mentioned method for preparing a 10kV cable low-smoke halogen-free flame-retardant sheath material, comprising the following raw materials in parts by weight: polyethylene 33-35 parts, EVA265 15-17 parts, POE-g-GMA 5-7 parts, aluminum hydroxide 16-17 parts, magnesium hydroxide 11-12 parts, flame-retardant masterbatch 9-10 parts, dipentaerythritol 3-4 parts, melamine urate 2-3 parts, antioxidant 1010 0.6-0.8 parts, antioxidant 168 0.4-0.6 parts, silicone 3-4.5 parts, polyethylene wax 1.5-2 parts, zinc stearate 1-1.5 parts, and stearic acid 0.5-0.7 parts.
[0022] Optionally, the flame retardant masterbatch comprises the following raw materials in parts by weight: 9-10 parts of ammonium polyphosphate type II, 0.2-0.3 parts of emulsifier OP-10, 2.5-3.5 parts of tetraethyl orthosilicate, 0.5-0.8 parts of vinyltriethoxysilane, 1.5-2 parts of aluminum nitrate nonahydrate, and 0.8-1 parts of urea.
[0023] The above-described technical solution of the present invention has at least the following beneficial effects: This invention uses ammonium polyphosphate as a raw material, forming a silicon-oxygen interlayer through the hydrolysis and condensation of tetraethyl orthosilicate and vinyltriethoxysilane. Then, an aluminum hydroxide outer layer is deposited on its surface using aluminum nitrate nonahydrate, resulting in a flame-retardant masterbatch with an ammonium polyphosphate core, a silicon-oxygen interlayer, and an aluminum hydroxide outer layer. The silicon-oxygen interlayer isolates the ammonium polyphosphate core and fixes the aluminum hydroxide outer layer through a Si-O-Al interface structure. The hydroxyl groups of the aluminum hydroxide outer layer interact with EVA265, which facilitates the dispersion of the flame-retardant masterbatch in the polyethylene substrate. During combustion, aluminum hydroxide and magnesium hydroxide decompose endothermically to generate Al2O3 and MgO. Ammonium polyphosphate catalyzes the dehydration of dipentaerythritol and part of the polyethylene substrate to form char. Melamine urate decomposes to release non-flammable gases and promotes char layer formation. The silicon-oxygen structure, together with Al2O3 and MgO, enhances the density and integrity of the char layer, thereby improving the smoke suppression and flame-retardant properties of the sheath material.
[0024] This invention uses flame-retardant masterbatch to partially replace pure inorganic flame-retardant particles such as aluminum hydroxide and magnesium hydroxide, reducing the amount of pure inorganic flame-retardant particles used while maintaining the flame-retardant properties of the sheath material. The ammonium polyphosphate, silicon-oxygen interlayer, and aluminum hydroxide outer layer in the flame-retardant masterbatch are combined into composite particles, which reduces agglomeration and interface defects caused by the independent dispersion of inorganic flame-retardant particles. Simultaneously, the interaction between the aluminum hydroxide outer layer and EVA265 improves the dispersion uniformity of the flame-retardant masterbatch in the polyethylene-based mixed matrix, reducing stress concentration and crack initiation, thereby improving the tensile strength and elongation at break of the sheath material. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. The described embodiments are some embodiments of the present invention, and all other embodiments obtained by those skilled in the art based on the described embodiments of the present invention are within the scope of protection of the present invention.
[0026] Example 1 Mix 10 parts of ammonium polyphosphate type II, 20 parts of anhydrous ethanol, and 10 parts of deionized water thoroughly. Adjust the pH to 10 with ammonia water. Add 0.3 parts of emulsifier OP-10, heat to 45°C, and stir at 500 rpm for 20 minutes. Add 3.5 parts of tetraethyl orthosilicate, and continue stirring for 4 hours. Add 0.8 parts of vinyltriethoxysilane (model A-151), raise the temperature to 65°C, and stir for 2 hours. Filter, wash four times with anhydrous ethanol, and vacuum dry at 70°C for 2 hours to obtain the pretreated product. After granulation, the granules were added to 20 parts of anhydrous ethanol and stirred at 800 rpm for 30 min to obtain a dispersion. 2 parts of aluminum nitrate nonahydrate were dissolved in 20 parts of deionized water and added to the dispersion. The mixture was stirred at 600 rpm for 60 min, 1 part of urea was added, and the pH was adjusted to 6 with acetate / sodium acetate buffer. The mixture was heated to 80℃ and stirred for 3 h. After centrifugation, the mixture was washed 3 times each with anhydrous ethanol and deionized water, dried under vacuum at 80℃ for 10 h, pulverized, and passed through a 200-mesh sieve to obtain flame retardant masterbatch.
[0027] Pour 17 parts of EVA265 into a mixer and heat to 110°C. Mix until the EVA265 is fully softened. Mix 17 parts of aluminum hydroxide, 12 parts of magnesium hydroxide and 10 parts of flame retardant masterbatch evenly, then pour into the mixer in 5 batches. Mix at 30 rpm for 12 minutes. Discharge the material, cool to room temperature and crush into 2-3 mm particles to obtain the composite flame retardant.
[0028] The following ingredients were added: 35 parts polyethylene (model: MPE1018), 7 parts POE-g-GMA (glycidyl methacrylate grafted ethylene-octene copolymer), 56 parts composite flame retardant, 4 parts dipentaerythritol, 3 parts melamine urate (CAS: 37640-57-6), 0.8 parts antioxidant 1010, 0.6 parts antioxidant 168, and 4.5 parts silicone (model: MB50). 315), 2 parts polyethylene wax, 1.5 parts zinc stearate and 0.7 parts stearic acid are mixed and stirred at 800 rpm for 10 minutes. The mixture is then poured into a mixer, heated to 105°C and mixed for 20 minutes. The mixture is then poured into a flat vulcanizing machine, heated to 160°C, and molded at 9 MPa for 15 minutes. After cooling and shaping, the sheath material is obtained.
[0029] Example 2 Nine parts of ammonium polyphosphate type II, 18 parts of anhydrous ethanol, and 9 parts of deionized water were mixed evenly. Ammonia water was added to adjust the pH to 9.5. 0.2 parts of emulsifier OP-10 were added, and the mixture was heated to 40°C and stirred at 400 rpm for 10 min. 2.5 parts of tetraethyl orthosilicate were added, and the reaction was continued with stirring for 3 h. 0.5 parts of vinyltriethoxysilane (model A-151) were added, and the mixture was heated to 60°C and stirred for 1 h. After filtration, the mixture was washed three times with anhydrous ethanol and dried under vacuum at 60°C for 1 h to obtain pretreated particles. Then, 15 parts of anhydrous ethanol were added and stirred at 600 rpm for 20 min to obtain a dispersion. 1.5 parts of aluminum nitrate nonahydrate were dissolved in 15 parts of deionized water and added to the dispersion. The mixture was stirred at 400 rpm for 30 min. 0.8 parts of urea were added, and the pH was adjusted to 5.5 with acetate / sodium acetate buffer. The mixture was heated to 75°C and stirred for 2 h. After centrifugation, the mixture was washed twice with anhydrous ethanol and twice with deionized water. It was then vacuum dried at 75°C for 8 h, pulverized, and passed through a 200-mesh sieve to obtain flame retardant masterbatch.
[0030] Pour 15 parts of EVA265 into a mixer, heat to 100℃, and mix until the EVA265 is fully softened; mix 16 parts of aluminum hydroxide, 11 parts of magnesium hydroxide and 9 parts of flame retardant masterbatch evenly, then pour into the mixer in 3 batches, mix at 20 rpm for 8 minutes, discharge, cool to room temperature and crush into 2-3 mm particles to obtain composite flame retardant.
[0031] The following ingredients were added: 33 parts polyethylene (model: MPE1018), 5 parts POE-g-GMA (glycidyl methacrylate grafted ethylene-octene copolymer), 51 parts composite flame retardant, 3 parts dipentaerythritol, 2 parts melamine urate (CAS: 37640-57-6), 0.6 parts antioxidant 1010, 0.4 parts antioxidant 168, and 3 parts silicone (model: MB50). 315), 1.5 parts polyethylene wax, 1 part zinc stearate and 0.5 parts stearic acid are mixed and stirred at 500 rpm for 5 minutes. The mixture is then poured into a mixer, heated to 100°C and mixed for 15 minutes. The mixture is then poured into a flat vulcanizing machine, heated to 150°C, and molded at 8 MPa for 10 minutes. After cooling and shaping, the sheath material is obtained.
[0032] Example 3 Mix 9.5 parts of ammonium type II polyphosphate, 19 parts of anhydrous ethanol, and 9.5 parts of deionized water thoroughly. Adjust the pH to 9.8 with ammonia. Add 0.25 parts of emulsifier OP-10, heat to 43°C, and stir at 450 rpm for 15 minutes. Add 3 parts of tetraethyl orthosilicate, and continue stirring for 3.5 hours. Add 0.6 parts of vinyltriethoxysilane (model A-151), raise the temperature to 62°C, and stir for 1.5 hours. Filter, wash three times with anhydrous ethanol, and vacuum dry at 65°C for 1.5 hours to obtain the pre-… After processing the particles, they were poured into 18 parts of anhydrous ethanol and stirred at 600 rpm for 25 min to obtain a dispersion. 1.6 parts of aluminum nitrate nonahydrate were dissolved in 17 parts of deionized water and poured into the dispersion. The mixture was stirred at 500 rpm for 40 min, 0.9 parts of urea were added, and the pH was adjusted to 5.5 with acetate / sodium acetate buffer. The mixture was heated to 77°C and stirred for 2.5 h. After centrifugation, the mixture was washed twice with anhydrous ethanol and twice with deionized water. It was then vacuum dried at 76°C for 9 h, pulverized, and passed through a 200-mesh sieve to obtain flame retardant masterbatch.
[0033] Pour 16 parts of EVA265 into a mixer and heat to 105℃. Mix until the EVA265 is fully softened. Mix 16.5 parts of aluminum hydroxide, 11.5 parts of magnesium hydroxide and 9.5 parts of flame retardant masterbatch evenly, and then pour them into the mixer in 4 batches. Mix at 25 rpm for 10 minutes. Discharge the material, cool to room temperature and then crush into 2-3 mm particles to obtain the composite flame retardant.
[0034] The following ingredients were added: 34 parts polyethylene (model: MPE1018), 6 parts POE-g-GMA (glycidyl methacrylate grafted ethylene-octene copolymer), 52 parts composite flame retardant, 3.5 parts dipentaerythritol, 2.5 parts melamine urate (CAS: 37640-57-6), 0.7 parts antioxidant 1010, 0.5 parts antioxidant 168, and 4 parts silicone (model: MB50). 315), 1.8 parts polyethylene wax, 1.2 parts zinc stearate and 0.6 parts stearic acid are mixed and stirred at 600 rpm for 7 minutes. The mixture is then poured into a mixer, heated to 102°C and mixed for 18 minutes. The mixture is then poured into a flat vulcanizing machine, heated to 158°C, and molded at 8.5 MPa for 12 minutes. After cooling and shaping, the sheath material is obtained.
[0035] Example 4 9.7 parts of ammonium polyphosphate type II, 19.5 parts of anhydrous ethanol, and 9.5 parts of deionized water were mixed evenly. Ammonia water was added to adjust the pH to 9.7. 0.27 parts of emulsifier OP-10 were added, and the mixture was heated to 43°C and stirred at 450 rpm for 17 min. 2.8 parts of tetraethyl orthosilicate were added, and the reaction was continued with stirring for 3 h. 0.7 parts of vinyltriethoxysilane (model A-151) were added, and the mixture was heated to 61°C and stirred for 2 h. After filtration, the mixture was washed four times with anhydrous ethanol and dried under vacuum at 67°C for 1.5 h to obtain the desired product. After pretreatment, the particles were poured into 19 parts of anhydrous ethanol and stirred at 700 rpm for 20 min to obtain a dispersion. 1.8 parts of aluminum nitrate nonahydrate were dissolved in 18 parts of deionized water and poured into the dispersion. The mixture was stirred at 500 rpm for 45 min. 0.85 parts of urea were added, and the pH was adjusted to 6 with acetate / sodium acetate buffer. The mixture was heated to 80°C and stirred for 3 h. After centrifugation, the particles were washed twice with anhydrous ethanol and twice with deionized water. The mixture was vacuum dried at 80°C for 8 h, pulverized, and passed through a 200-mesh sieve to obtain flame retardant masterbatch.
[0036] Pour 15.5 parts of EVA265 into a mixer and heat to 102℃. Mix until the EVA265 is fully softened. Mix 16.7 parts of aluminum hydroxide, 11.5 parts of magnesium hydroxide and 9.5 parts of flame retardant masterbatch evenly, and then pour them into the mixer in 3 batches. Mix at 20 rpm for 12 minutes. Discharge the material, cool it to room temperature and then crush it into 2-3 mm particles to obtain the composite flame retardant.
[0037] The mixture consists of 33.5 parts polyethylene (model: MPE1018), 6.5 parts POE-g-GMA (glycidyl methacrylate grafted ethylene-octene copolymer), 53 parts composite flame retardant, 3.8 parts dipentaerythritol, 2.4 parts melamine urate (CAS: 37640-57-6), 0.72 parts antioxidant 1010, 0.53 parts antioxidant 168, and 4.2 parts silicone (model: MB50). 315), 1.7 parts polyethylene wax, 1.2 parts zinc stearate and 0.63 parts stearic acid are mixed and stirred at 500 rpm for 10 min. The mixture is poured into a mixer, heated to 103℃ and mixed for 17 min. The mixture is then poured into a flat vulcanizing machine, heated to 157℃ and molded at 9 MPa for 10 min. After cooling and shaping, the sheath material is obtained.
[0038] Example 5 9.3 parts of ammonium polyphosphate type II, 18.4 parts of anhydrous ethanol, and 9.3 parts of deionized water were mixed evenly. Ammonia water was added to adjust the pH to 9.6. 0.22 parts of emulsifier OP-10 were added, and the mixture was heated to 42°C and stirred at 500 rpm for 15 min. 3.2 parts of tetraethyl orthosilicate were added, and the reaction was continued with stirring for 3.5 h. 0.65 parts of vinyltriethoxysilane (model A-151) were added, and the mixture was heated to 63°C and stirred for 1.5 h. After filtration, the mixture was washed three times with anhydrous ethanol and dried under vacuum at 63°C for 2 h to obtain the desired product. After pretreatment, the particles were added to 20 parts of anhydrous ethanol and stirred at 800 rpm for 30 min to obtain a dispersion. 1.7 parts of aluminum nitrate nonahydrate were dissolved in 17 parts of deionized water and added to the dispersion. The mixture was stirred at 450 rpm for 60 min. 1 part of urea was added, and the pH was adjusted to 5.5 with acetate / sodium acetate buffer. The mixture was heated to 78°C and stirred for 2.5 h. After centrifugation, the particles were washed three times each with anhydrous ethanol and deionized water. The mixture was then vacuum dried at 78°C for 9 h, pulverized, and passed through a 200-mesh sieve to obtain flame retardant masterbatch.
[0039] Pour 16 parts of EVA265 into a mixer, heat to 100℃, and mix until the EVA265 is fully softened. Mix 17 parts of aluminum hydroxide, 12 parts of magnesium hydroxide, and 9 parts of flame retardant masterbatch evenly, then pour them into the mixer in 4 batches and mix at 30 rpm for 12 minutes. Discharge the material, cool it to room temperature, and then crush it into 2-3 mm particles to obtain the composite flame retardant.
[0040] The mixture consisted of 34 parts polyethylene (model: MPE1018), 6.5 parts POE-g-GMA (glycidyl methacrylate grafted ethylene-octene copolymer), 53 parts composite flame retardant, 3.5 parts dipentaerythritol, 2.4 parts melamine urate (CAS: 37640-57-6), 0.7 parts antioxidant 1010, 0.5 parts antioxidant 168, and 3.8 parts silicone (model: MB50). 315), 1.7 parts polyethylene wax, 1.3 parts zinc stearate and 0.6 parts stearic acid are mixed and stirred at 500 rpm for 10 min. The mixture is poured into a mixer, heated to 105℃ and mixed for 18 min. The mixture is then poured into a flat vulcanizing machine, heated to 155℃ and molded at 8.5 MPa for 15 min. After cooling and shaping, the sheath material is obtained.
[0041] Example 6 Mix 10 parts of ammonium polyphosphate type II, 20 parts of anhydrous ethanol, and 10 parts of deionized water thoroughly. Adjust the pH to 10 with ammonia water. Add 0.3 parts of emulsifier OP-10, heat to 45°C, and stir at 500 rpm for 20 minutes. Add 3.5 parts of tetraethyl orthosilicate, and continue stirring for 4 hours. Add 0.8 parts of vinyltriethoxysilane (model A-151), raise the temperature to 65°C, and stir for 2 hours. Filter, wash four times with anhydrous ethanol, and vacuum dry at 70°C for 2 hours to obtain the pretreated product. After granulation, the granules were added to 20 parts of anhydrous ethanol and stirred at 800 rpm for 30 min to obtain a dispersion. 2 parts of aluminum nitrate nonahydrate were dissolved in 20 parts of deionized water and added to the dispersion. The mixture was stirred at 600 rpm for 60 min, 1 part of urea was added, and the pH was adjusted to 6 with acetate / sodium acetate buffer. The mixture was heated to 80℃ and stirred for 3 h. After centrifugation, the mixture was washed 3 times each with anhydrous ethanol and deionized water, dried under vacuum at 80℃ for 10 h, pulverized, and passed through a 200-mesh sieve to obtain flame retardant masterbatch.
[0042] The following ingredients were added: 35 parts polyethylene (MPE1018), 7 parts POE-g-GMA (glycidyl methacrylate grafted ethylene-octene copolymer), 17 parts EVA265, 17 parts aluminum hydroxide, 12 parts magnesium hydroxide, 10 parts flame retardant masterbatch, 4 parts dipentaerythritol, 3 parts melamine urate (CAS: 37640-57-6), 0.8 parts antioxidant 1010, 0.6 parts antioxidant 168, and 4.5 parts silicone (MB50). 315), 2 parts polyethylene wax, 1.5 parts zinc stearate and 0.7 parts stearic acid are mixed and stirred at 800 rpm for 10 minutes. The mixture is then poured into a mixer, heated to 105°C and mixed for 20 minutes. The mixture is then poured into a flat vulcanizing machine, heated to 160°C, and molded at 9 MPa for 15 minutes. After cooling and shaping, the sheath material is obtained.
[0043] The present invention also includes comparative examples and related experiments.
[0044] Comparative Example 1 The only difference from Example 1 is that pretreated particles are used instead of flame-retardant masterbatch, while the other components and preparation steps are completely the same, resulting in a sheath material.
[0045] Comparative Example 2 The only difference from Example 1 is that EVA265 was not added; the other components and preparation steps are completely the same, resulting in a sheath material.
[0046] Comparative Example 3 The only difference from Example 1 is that tetraethyl orthosilicate and vinyltriethoxysilane are not added during the preparation of the flame retardant masterbatch. The other components and preparation steps are completely the same, and the sheath material is obtained.
[0047] Performance testing: Mechanical properties: The tensile strength and elongation at break of the sheath materials prepared in Examples 1-6 and Comparative Examples 1-3 were tested in accordance with the national standard GB / T 1040.2-2022. The test results are shown in Table 1.
[0048] Flame retardancy: The vertical flammability (L) of the sheath materials prepared in Examples 1-6 and Comparative Examples 1-3 was tested according to national standard GB / T 2408-2021; the limiting oxygen index (LOI) of the sheath materials prepared in Examples 1-6 and Comparative Examples 1-3 was tested according to national standard GB / T 2406.2-2009; and the flame retardancy was tested at a radiation irradiance of 25 kW / m² according to national standard GB / T 8323.2-2008. 2 Under the conditions, the smoke density D of the sheath materials prepared in Examples 1-6 and Comparative Examples 1-3 was tested in two modes: with and without ignition flame. The test results are shown in Table 1.
[0049] Table 1
[0050] As shown in Table 1, the 10kV cable low-smoke halogen-free flame-retardant sheath materials prepared in Examples 1-6 all exhibit good tensile strength and elongation at break, with a vertical flammability rating (L) reaching V-0. They also possess a high limiting oxygen index (LOI) and a low smoke density (D), indicating that the sheath materials prepared in this invention have excellent mechanical and flame-retardant properties. Compared to Examples 1-5, in Example 6, EVA265, aluminum hydroxide, magnesium hydroxide, and flame-retardant masterbatch were directly mixed and kneaded with other raw materials. This resulted in a decrease in elongation at break and a significant increase in smoke density (D), suggesting that pre-mixing EVA265, aluminum hydroxide, magnesium hydroxide, and flame-retardant masterbatch into a composite flame retardant is beneficial for further improving the mechanical and flame-retardant properties of the sheath material.
[0051] Compared to Example 1, Comparative Example 1 used pretreated particles instead of flame-retardant masterbatch, resulting in a decrease in the limiting oxygen index (LOI) and vertical burning rating (L) of the resulting sheath material, while the smoke density (D) increased. This indicates that the pretreated particles, treated with aluminum nitrate nonahydrate and urea, help improve the flame-retardant and smoke-suppressing properties of the sheath material. Compared to Example 1, Comparative Example 2 did not add EVA265, resulting in a significant decrease in the tensile strength, elongation at break, and limiting oxygen index of the resulting sheath material, while the smoke density (D) significantly increased. This indicates that the interaction between the flame-retardant masterbatch and EVA265 is beneficial to improving the mechanical properties, flame-retardant properties, and smoke-suppressing properties of the sheath material. Comparative Example 3 did not add tetraethyl orthosilicate and vinyltriethoxysilane during the preparation of the flame-retardant masterbatch, and the resulting sheath material had a lower limiting oxygen index (LOI), vertical burning rating (L), and smoke density (D) than that of Example 1. This indicates that the treatment of ammonium polyphosphate with tetraethyl orthosilicate and vinyltriethoxysilane helps improve the flame-retardant and smoke-suppressing properties of the sheath material.
[0052] The above are preferred embodiments of the present invention. Those skilled in the art can make several improvements and modifications without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a low-smoke, halogen-free, flame-retardant sheath material for 10kV cables, characterized in that, The preparation steps include the following: S1. Mix ammonium polyphosphate, anhydrous ethanol and deionized water evenly, adjust the pH to alkaline, add emulsifier, heat and stir, add tetraethyl orthosilicate, stir to react, add vinyltriethoxysilane, heat to react, filter, wash and dry, and after obtaining pretreated particles, pour into anhydrous ethanol to obtain a dispersion. S2. Dissolve aluminum nitrate nonahydrate in deionized water, pour into the dispersion, add urea, adjust the pH to weakly acidic, heat and stir, centrifuge, wash and dry, pulverize and sieve to obtain flame retardant masterbatch. S3. Mix polyethylene, POE-g-GMA, EVA265, aluminum hydroxide, magnesium hydroxide, flame retardant masterbatch, dipentaerythritol, melamine urate, antioxidant, silicone, polyethylene wax, zinc stearate, and stearic acid evenly, knead, mold, cool and set to obtain sheath material; pre-mix EVA265, aluminum hydroxide, magnesium hydroxide, and flame retardant masterbatch into a composite flame retardant, and then mix it evenly with other raw materials; The preparation method of the composite flame retardant includes the following steps: EVA265 is poured into a mixer and heated to 100~110℃ for mixing and softening. After aluminum hydroxide, magnesium hydroxide and flame retardant masterbatch are mixed evenly, they are poured into the mixer in 3~5 batches and mixed at a speed of 20~30rpm for 8~12min. The material is then discharged and crushed to obtain the composite flame retardant. The weight proportions of each raw material are as follows: polyethylene 33-35 parts, POE-g-GMA 5-7 parts, EVA265 15-17 parts, aluminum hydroxide 16-17 parts, magnesium hydroxide 11-12 parts, flame retardant masterbatch 9-10 parts, dipentaerythritol 3-4 parts, melamine urate 2-3 parts, antioxidant 1010 0.6-0.8 parts, antioxidant 168 0.4-0.6 parts, silicone 3-4.5 parts, polyethylene wax 1.5-2 parts, zinc stearate 1-1.5 parts, and stearic acid 0.5-0.7 parts.
2. The method for preparing a low-smoke, halogen-free, flame-retardant sheath material for 10kV cables according to claim 1, characterized in that, In step S3, polyethylene, POE-g-GMA, composite flame retardant, dipentaerythritol, melamine urate, antioxidant 1010, antioxidant 168, silicone, polyethylene wax, zinc stearate and stearic acid are mixed evenly, heated to 100~105℃ and kneaded for 15~20 minutes, then molded, cooled and shaped to obtain the sheath material.
3. The method for preparing a low-smoke, halogen-free, flame-retardant sheath material for 10kV cables according to claim 1, characterized in that, In step S1, ammonium polyphosphate type II, anhydrous ethanol, and deionized water are mixed evenly, ammonia water is added to adjust the pH to 9.5-10, emulsifier OP-10 is added, the mixture is heated to 40-45℃, stirred at 400-500 rpm for 10-20 min, tetraethyl orthosilicate is added, and the reaction is continued to be stirred for 3-4 h, vinyltriethoxysilane is added, the temperature is raised to 60-65℃ and stirred for 1-2 h, the mixture is filtered, washed 3-4 times with anhydrous ethanol, and vacuum dried to obtain pretreated particles. These particles are then poured into anhydrous ethanol and stirred at 600-800 rpm for 20-30 min to obtain a dispersion.
4. The method for preparing a low-smoke, halogen-free, flame-retardant sheath material for 10kV cables according to claim 1, characterized in that, In step S2, aluminum nitrate nonahydrate is dissolved in deionized water, poured into the dispersion, stirred at 400-600 rpm for 30-60 min, urea is added, and the pH is adjusted to 5.5-6 with acetate / sodium acetate buffer. The mixture is heated to 75-80℃ and stirred for 2-3 h. After centrifugation, the mixture is washed 2-3 times each with anhydrous ethanol and deionized water, vacuum dried, pulverized, and passed through a 200-mesh sieve to obtain flame retardant masterbatch.
5. The method for preparing a low-smoke, halogen-free, flame-retardant sheath material for 10kV cables according to claim 1, characterized in that, In step S3, polyethylene, POE-g-GMA, EVA265, aluminum hydroxide, magnesium hydroxide, flame retardant masterbatch, dipentaerythritol, melamine urate, antioxidant 1010, antioxidant 168, silicone, polyethylene wax, zinc stearate, and stearic acid are mixed evenly, heated to 100~105℃ and kneaded for 15~20 minutes, then molded, cooled and shaped to obtain the sheath material.
6. The method for preparing a low-smoke, halogen-free, flame-retardant sheath material for 10kV cables according to claim 1, characterized in that, The molding process is carried out at a temperature of 150~160℃ and a pressure of 8~9MPa.
7. A low-smoke, halogen-free, flame-retardant sheath material for 10kV cables, prepared using the method described in any one of claims 1 to 6, characterized in that... The raw materials include the following parts by weight: 33-35 parts polyethylene, 5-7 parts POE-g-GMA, 15-17 parts EVA265, 16-17 parts aluminum hydroxide, 11-12 parts magnesium hydroxide, 9-10 parts flame retardant masterbatch, 3-4 parts dipentaerythritol, 2-3 parts melamine urate, 0.6-0.8 parts antioxidant 1010, 0.4-0.6 parts antioxidant 168, 3-4.5 parts silicone, 1.5-2 parts polyethylene wax, 1-1.5 parts zinc stearate, and 0.5-0.7 parts stearic acid.
8. The low-smoke, halogen-free, flame-retardant sheath material for 10kV cables according to claim 7, characterized in that, The flame retardant masterbatch comprises the following raw materials in parts by weight: 9-10 parts of ammonium polyphosphate type II, 0.2-0.3 parts of emulsifier OP-10, 2.5-3.5 parts of tetraethyl orthosilicate, 0.5-0.8 parts of vinyltriethoxysilane, 1.5-2 parts of aluminum nitrate nonahydrate, and 0.8-1 parts of urea.
Citation Information
Patent Citations
B1-grade low-smoke halogen-free cable sheath material and preparation method thereof
CN112662042A
Low-smoke halogen-free flame-retardant B1-grade polyolefin cable sheath material and preparation method thereof
CN111117054A
Halogen-free low-smoke flame-retardant polyolefin sheath material and preparation method thereof
CN115746445A